2015
DOI: 10.4314/ijbcs.v9i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversité floristique et régénération naturelle sur les Hautes Terre de Lebialem (Ouest Cameroun)

Abstract: Afin d'évaluer la diversité floristique, la structure du peuplement et la régénération naturelle, le présent travail a été mené sur les Hautes Terres de Lebialem dans la forêt de Bangang (Ouest Cameroun). Au total, 10 relevés floristiques de 250 m x 20 m ont été réalisés ; 6 sous parcelles de 100 m x 20 m ont été aussi établies dans 6 des 10 relevés. A l'intérieur de chaque relevé, tous les individus ayant un diamètre ≥10 cm à 1,30 m de hauteur ont été pris en compte. Pour les sous parcelles, les diamètres com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
0
13
1
9
Order By: Relevance
“…La dominance des espèces de la région Guinéo-Congolaise (GC) est une preuve que cette zone appartient bien à la région GuinéoCongolaise (Tiokeng, 2015). La proportion des espèces Guinéo-Congolaise qui tend vers 80% confirme l'assertion de Solefack (2018) qui soutient que la flore de cette région phytogéographique doit avoir plus de 80 à 90% d'endémiques et seulement environ 10% d'espèces d'autres régions phytogéographiques.…”
Section: Discussionunclassified
“…La dominance des espèces de la région Guinéo-Congolaise (GC) est une preuve que cette zone appartient bien à la région GuinéoCongolaise (Tiokeng, 2015). La proportion des espèces Guinéo-Congolaise qui tend vers 80% confirme l'assertion de Solefack (2018) qui soutient que la flore de cette région phytogéographique doit avoir plus de 80 à 90% d'endémiques et seulement environ 10% d'espèces d'autres régions phytogéographiques.…”
Section: Discussionunclassified
“…Concerning Enantia olivacea, the aqueous decoction from its stem bark is drunk against intestinal worms, intestinal spasms and asthenia while the stem bark of Massularia acuminata is used, as an aqueous decoction, to treat liver diseases, back pain, hemorrhoids, premature ejaculation and erectile dysfunction (Yakubu et al, 2008;Muganza et al, 2012;Sangare et al, 2012). The stem bark of Massularia acuminata is also used as chewing stick for oral hygiene whereas the juice from its fruit is used against conjunctivitis (Gill, 1992;Ndukwe et al, 2004;Tiokeng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In well diversified forests of Central Africa, Kenfack et al (2007) and Gourlet-Fleury et al (2012) found Fisher's α > 30 and this corresponded to richness of more than 87 species ha -1 against 12 to 16 species ha -1 in Lama forest. Moreover, in the highlands of Lebialem (Bangang forest, Western Cameroun), a 48 to 72 species per ha and a maximal diversity (2.97 < H' < 5.80 bits and 0.52 < Eq < 0.96) was observed by Tiokeng et al (2015). Therefore Lama forests are less diversified than those of Central Africa.…”
Section: Comparison Of Structural Attributes According To Forest Stagmentioning
confidence: 99%
“…Therefore Lama forests are less diversified than those of Central Africa. Higher diversity, in less-disturbed vegetation, is determined by niche variability and therefore the variability of biotic and abiotic factors favorable to the development of several species (Tiokeng et al, 2015). Among the abiotic factors, soil properties affected the establishment of tree species (Olatunji et al, 2015), and it may be the case due to the vertisols (black-cotton ill drained soil) in Lama forest.…”
Section: Comparison Of Structural Attributes According To Forest Stagmentioning
confidence: 99%